Comparing the performance on the MI and SAT/PSAT for the purpose of monitoring student achievement - McDonald, Michael; Pang, Yulei (International Journal of Information and Education Technology, 2021)
This paper will discuss the correlation between the SAT and the Math Inventory Test. Many school districts adopted the Math Inventory as a tool to measure student growth from grades kindergarten through high school. The Math Inventory is a computer-administered test that gives students math problems spanning from counting to high school level math. When completed, the students are given a quantile measure, much like a Lexile score for reading skill. The purpose of this study is to figure out if success on the Math Inventory is a good indicator for performing well on the SAT. For most high schools around the United States, objectives and lessons are aligned with those of the SAT. The goal of high school teachers is for students to excel on the SAT so that they can go to college, which means the tests used in middle school should be aligned with that goal. If the Math Inventory is not, then it might not be a very good use of school time and resources. Data was analyzed from the 2017-2018 school year from ten different high schools in an urban school district to determine the correlation between Math Inventory score, and the math score/sub scores of SAT/PSAT. The value of the Pearson’s correlation coefficient is used to suggest a fairly moderate positive relationship between these two variables. © 2021, International Journal of Information and Education Technology. All rights reserved.
Keywords: dept.mat; peer-reviewed

CT-free attenuation correction for dedicated cardiac SPECT using a 3D dual squeeze-and-excitation residual dense network. - Chen, Xiongchao; Zhou, Bo; Shi, Luyao; Liu, Hui; Pang, Yulei; Wang, Rui; Miller, Edward J.; Sinusas, Albert J.; Liu, Chi (Journal of nuclear cardiology : official publication of the American Society of Nuclear Cardiology, 2021)
Background: Attenuation correction (AC) using CT transmission scanning enables the accurate quantitative analysis of dedicated cardiac SPECT. However, AC is challenging for SPECT-only scanners. We developed a deep learning-based approach to generate synthetic AC images from SPECT images without AC. Methods: CT-free AC was implemented using our customized Dual Squeeze-and-Excitation Residual Dense Network (DuRDN). 172 anonymized clinical hybrid SPECT/CT stress/rest myocardial perfusion studies were used in training, validation, and testing. Additional body mass index (BMI), gender, and scatter-window information were encoded as channel-wise input to further improve the network performance. Results: Quantitative and qualitative analysis based on image voxels and 17-segment polar map showed the potential of our approach to generate consistent SPECT AC images. Our customized DuRDN showed superior performance to conventional network design such as U-Net. The averaged voxel-wise normalized mean square error (NMSE) between the predicted AC images by DuRDN and the ground-truth AC images was 2.01 ± 1.01%, as compared to 2.23 ± 1.20% by U-Net. Conclusions: Our customized DuRDN facilitates dedicated cardiac SPECT AC without CT scanning. DuRDN can efficiently incorporate additional patient information and may achieve better performance compared to conventional U-Net. © 2021, American Society of Nuclear Cardiology.
Keywords: adult; article; body mass; controlled study; deep learning; dept.mat; excitation; female; gender; human; male; myocardial perfusion imaging; patient information; peer-reviewed; physiological stress; qualitative analysis; quantitative analysis; single photon emission computed tomography; x-ray computed tomography

Inter-pass motion correction for whole-body dynamic parametric PET imaging - Guo, Xueqi; Wu, Jing; Chen, Ming-Kai; Onofrey, John A.; Pang, Yulei; Pigg, David; Casey, Michael E.; Dvornek, Nicha C.; Liu, Chi (The Journal of Nuclear Medicine, 2021)
Keywords: dept.mat; peer-reviewed; ⛔ No DOI found